Game Playing - *, Komal; Hazrati, Karuna; Mittal, Priyanka (IJRDO -Journal of Computer Science Engineering, 2015)
Computer games are an increasingly popular application for Artiﬁcial Intelligence (AI) research, and conversely AI is an increasingly popular selling point for commercial games. Although games are typically associated with entertainment, there are many “serious” applications of gaming, including military, corporate, and advertising applications. There are also so-called “humane” gaming applications for medical training, educational games, and games that reﬂect social consciousness or advocate for a cause. Game AI is the effort of going beyond scripted interactions, however complex, into the arena of truly interactive systems that are responsive, adaptive, and intelligent. Such systems learn about the player(s) during game play, adapt their own behaviours beyond the pre-programmed set provided by the game author, and interactively develop and provide a richer experience to the player(s).